Quadratic maps with maximal oscillation - Hofbauer, Franz; Keller, Gerhard (Algorithms, fractals, and dynamics (Okayama/Kyoto, 1992), 1995)
Let (f t )o≤t≤1 denote the family of quadratic maps f t(x) = 2t(1- x 2) - 1 on [-1, 1]. An important aspect of the asymptotics of interates of a map f t is the behaviour of mass distributions along individual orbits.